Combination of structural and microstructural effects in the multiferroic response of Nd and Ti co-doped BiFeO3 bulk ceramics. Issue 5 (1st April 2019) - Gumiel, C.; Jardiel, T.; Bernardo, M.S.; Villanueva, P.G.; Urdiroz, U.; Cebollada, F.; Aragó, C.; Caballero, A.C.; Peiteado, M.
Abstract: Different dopant strategies are currently under investigation in order to overcome the many problems that limit the commercial viability of BiFeO3 -based ceramic devices. Neodymium substitution onto the A site of the perovskite lattice provokes significant changes in the crystal structure of the parent material which can derive in enhanced multiferroic properties, but the conductivity in the bulk system is still too high. Titanium doping on the other hand generates a distinctive micro-nanostructure in the consolidated ceramics which can largely increase the dc resistivity of the whole material. A combination of these two effects is here attempted in a co-doping approach which evidences that the microstructural effect caused upon Ti-doping, provoking a reduction of the leakage currents, eventually allows the co-doped material to capitalize on the unique piezoelectric and magnetic properties structurally triggered by the Nd-doping.